2015
DOI: 10.1177/1534734614568374
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of Therapeutic Magnetic Resonance in the Management of Postsurgical Lesion of the Diabetic Foot

Abstract: To evaluate the safety and effectiveness of therapeutic magnetic resonance (TMR) in the management of the diabetic foot (DF), we treated a group of consecutive type 2 diabetic inpatients with wide postsurgical lesions (Group A: N = 10; age 67.7 ± 18.9 years, duration of diabetes 22.3 ± 6.6 years, 8.1 ± 1.1%, body mass index 29.4 ± 2.1 kg/m(2)), for 2 consecutive weeks, while admitted, with a low-intensity magnetic resonance equipment, in addition to standard treatment. Patients, compared with a matched control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…All were of high risk of bias or showed no evidence of benefit. One RCT study of therapeutic magnetic resonance therapy was at low risk of bias but showed no benefit on the healing of DFUs despite the promise of an earlier pilot …”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…All were of high risk of bias or showed no evidence of benefit. One RCT study of therapeutic magnetic resonance therapy was at low risk of bias but showed no benefit on the healing of DFUs despite the promise of an earlier pilot …”
Section: Recommendationsmentioning
confidence: 99%
“…One RCT study of therapeutic magnetic resonance therapy 107 was at low risk of bias but showed no benefit on the healing of DFUs despite the promise of an earlier pilot. 108 Overall, because of poor study design, it was concluded that there was little evidence to recommend the use of mechanical and physical therapies in the management of hard-to-heal diabetic foot ulcers. Rationale.…”
Section: Rationalementioning
confidence: 99%
“… 10-12 In particular, experiences in clinical settings have confirmed the safety and effectiveness of PEMFs through Therapeutic Magnetic Resonance (TMR R ) in promoting tissue repair in post-traumatic and chronic wounds, making this technology potentially interesting for the management of DFUs and post-surgical wounds. 13 , 14 Furthermore, in an i n vitro dermal-like tissue, we have previously demonstrated that TMR R enhances skin wound healing improving the quality of the extracellular matrix (ECM) and reducing ROS, leading to a positive rejuvenation effect on cells. 15 In the present work, we investigated, under clinical, cellular and molecular biology point of view, the influence of PEMFs on wound healing process in consecutive Type-2 diabetic patients, studying the granulation tissue of DFUs treated with TMR R .…”
Section: Introductionmentioning
confidence: 99%
“…One RCT on static magnetic therapy had a small sample size, randomization did not control for baseline differences between the two groups, and therefore, the results are difficult to interpret . A multicentre double‐blind RCT with a low risk of bias comparing twice daily application of therapeutic magnetic resonance for 4 weeks to usual care did not find a difference in ulcer healing at 10 weeks of follow‐up, in contrast to the findings from an earlier smaller, open observational pilot study …”
Section: Physical Therapiesmentioning
confidence: 65%
“…194 A multicentre doubleblind RCT with a low risk of bias comparing twice daily application of therapeutic magnetic resonance for 4 weeks 195 to usual care did not find a difference in ulcer healing at 10 weeks of follow-up, in contrast to the findings from an earlier smaller, open observational pilot study. 196…”
Section: Magnetic and Therapeutic Magnetic Resonance Therapiesmentioning
confidence: 99%